Objective Clinical Measurement Tools for Functional Evaluation of the Surgical Patient - Thomas, Jacob; Hall, Jamie B.; Schauffler, Rose; Guess, Trent M. (The Journal of Knee Surgery, 2023)
Following knee surgery, clinicians have traditionally used visually rated or time-based assessments of lower extremity movement quality to measure surgical outcomes, plan rehabilitation interventions, and measure success. These methods of assessment are prone to error and do not fully capture a patient's inefficient movement patterns post surgery. Further, currently available systems which objectively measure kinematics during these tasks are expensive and unidimensional. For these reasons, recent research has called for the development of objective and low-cost precision rehabilitation tools to improve clinical measurement of movement tasks. The purpose of this article is to highlight two such tools and their applications to knee surgery. The systems highlighted within this article are the Mizzou Point-of-Care Assessment System (MPASS) and the Mizzou Knee Arthrometer Testing System (MKATS). MPASS has demonstrated high levels of agreement with the gold-standard Vicon system in measuring kinematics during sit-to-stand (R > 0.71), lateral step-down (intraclass correlation coefficient [ICC] > 0.55, apart from ankle flexion), and drop vertical jump tasks (ICC > 0.62), as well as gait (R > 0.87). MKATS has been used to quantify differences in tibiofemoral motion between groups during lateral step-down, step-up-and-over, and step-up/step-down tasks. Objective measurement of clinical tasks using portable and inexpensive instruments, such as the MPASS and MKATS, can help clinicians identify inefficient movement patterns and asymmetries which may damage and wear down supporting structures within the knee and throughout the kinetic chain causing pain and discomfort. Identifying these issues can help clinicians to plan interventions and measure their progress at a lower cost than currently available systems. The MPASS and MKATS are useful tools which have many applications to knee surgery.
Keywords: precision rehabilitation; biomechanics; measurement; surgical outcomes